2020
DOI: 10.1159/000508792
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-331 Indicates Poor Prognosis and Promotes Progression of Breast Cancer

Abstract: Background: With the increasing number of cases of breast cancer every year, the exploration of novel biomarkers has drawn attention. miR-331 has been demonstrated to play a role in various cancers, but its role in breast cancer is still unknown. Methods: In this study, we included 121 patients with breast cancer treated at Affiliated Hospital of Weifang Medical University. Breast cancer tissues and adjacent normal tissues were collected during the surgery. The expression of miR-331 in breast cancer tissues an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…miR-331 was overexpressed in women in metastatic BC, not only when comparing with healthy controls, but also when comparing to women with non-invasive luminal-A BC [ 59 ]. Likewise, miR-331 was overexpressed in BC with lymph node metastasis, higher TNM stage and poor prognosis [ 60 ]. These publications are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…miR-331 was overexpressed in women in metastatic BC, not only when comparing with healthy controls, but also when comparing to women with non-invasive luminal-A BC [ 59 ]. Likewise, miR-331 was overexpressed in BC with lymph node metastasis, higher TNM stage and poor prognosis [ 60 ]. These publications are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR‐429 was commonly dysregulated in different cancers and could modulate cancer cell proliferation, motility, and drug resistance phenomena 14 . Jiang et al 15 also discovered that the high abundance of miR‐331 was associated with tumor metastasis BC. MiR‐144 was obviously downregulated in BC and could arrest BC progression in vitro by targeting centrosomal protein 55 16 .…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are important factors that affect the occurrence and development of various diseases such as breast cancer (17) and Parkinson's disease (18). Studies have suggested that various physiological and pathological processes of the nervous system are also affected by miRNAs, which have been identified as potential biomarkers of AD (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%